Hydroclimate of the Andes Part II: Hydroclimate Variability and Sub-Continental Patterns - Arias, Paola A.; Garreaud, René; Poveda, Germán; Espinoza, Jhan Carlo; Molina-Carpio, Jorge; Masiokas, Mariano; Viale, Maximiliano; Scaff, Lucia; van Oevelen, Peter J. (Frontiers in Earth Science, 2021)
This paper provides an updated review of the most relevant scientific literature related to the hydroclimate of the Andes. The Andes, the longest cordillera in the world, faces major challenges regarding climate variability and climate change, which impose several threats to sustainable development, including water supply and the sustainability of ecosystem services. This review focuses on hydroclimate variability of the Andes at a sub-continental scale. The annual water cycle and long-term water balance along the Andes are addressed first, followed by the examination of the effects of orography on convective and frontal precipitation through the study of precipitation gradients in the tropical, subtropical and extratropical Andes. In addition, a review is presented of the current scientific literature on the climate variability in the Andes at different timescales. Finally, open research questions are presented in the last section of this article.